Bisnis Media: Pasca Matinya Televisi Nasional Dalam Perspektif Jurnalistik - Ahmad Ahmad Toni (Jurnal Komunikasi, 2016)
ABSTRACTJustice information in socio-cultural perspective of the Indonesian nation is determined by the regulatory system of broadcasting that is healthy, it is characterized by the power of television Jakarta bersiaran in the archipelago with all the violence and the values of modernism that is not required by the subculture of the nation, even the things that are associated with regulation was dominated by the broadcasting authorities in Jakarta. Media conglomerates are widely blamed as the cause of the birth of symbols of violence against the nation's cultural pluralism, the control over the broadcasting rights and the system by media conglomerates into a global cultural colonization that is manifested through the broadcast contains the reference to Western culture. Broadcasting system that causes the death of flavors and tastes diversity owned the nation as a world cultural power. Nullifying the media conglomerate's system will show the broadcasting regulatory system in Indonesia is dominated by the global broadcasting system that would be affiliated with the barons and katrel domestic broadcasting. With the introduction of digital broadcasting system that diprakarsasi with the demise of the national television media is expected to grow the business system fair for all this people, by providing business space for new players with the capital area and the system of regional employment-based local culture as well. Content-based broadcast journalism in the broadcasting system in the future be a great opportunity to foster diversity kontenst release that are not controlled by media conglomerates. Content journalistic diversity to the birth indicator healthy broadcast system and represents the face of Indonesian archipelago in the broadcasting system.ABSTRAKSIKeadilan informasi dalam perspektif sosial budaya bangsa Indonesia ditentukan dengan sistem regulasi penyiaran yang sehat, hal ini ditandai dengan kuasa televisi Jakarta yang bersiaran di nusantara dengan segala kekerasan dan nilai-nilai modernisme yang tidak dibutuhkan oleh subbudaya bangsa, bahkan hal-hal yang berkaitan dengan regulasinya pun dikuasai oleh penguasa penyiaran Jakarta. Konglomerasi media yang banyak dituding sebagai penyebab lahirnya simbol-simbol kekerasan terhadap budaya pluralisme bangsa ini, penguasaan atas hak siar dan sistemnya oleh konglomerasi media menjadi penjajahan budaya global yang dimanifestasikan lewat kontent siaran yang mengacu kepada budaya Barat. Sistem penyiaran inilah yang menyebabkan matinya rasa dan selera keberagaman yang dimiliki bangsa sebagai kekuatan budaya dunia. Pembiaran atas kehendak sistem konglomerasi media ini menunjukan sistem regulasi penyiaran di Indonesia dikuasai oleh sistem penyiaran global yang tentunya berafiliasi dengan cukong-cukong dan katrel penyiaran dalam negeri. Dengan dicanangkannya sistem siaran digital yang diprakarsasi dengan matinya televisi nasional diharapkan tumbuh sistem bisnis media yang berkeadilan bagi segenap bangsa ini, dengan memberikan ruang bisnis kepada pemain baru dengan modal daerah dan sistem ketenagakerjaan daerah yang berbasis budaya lokal pula. Kontent siaran yang berbasis jurnalistik dalam sistem penyiaran kedepan menjadi peluang yang besar dalam menumbuhkan keberagaman kontenst siaran yang tidak dikuasai oleh konglomerasi media. Konten jurnalistik yang beragam menjadi indikator lahirnya sistem siaran yang sehat dan merepresentasikan wajah nusantara dalam sistem penyiaran Indonesia.